2011
DOI: 10.1051/0004-6361/201016206
|View full text |Cite
|
Sign up to set email alerts
|

The star cluster – field star connection in nearby spiral galaxies

Abstract: Context. Recent studies have started to cast doubt on the assumption that most stars are formed in clusters. Observational studies of field stars and star cluster systems in nearby galaxies can lead to better constraints on the fraction of stars forming in clusters. Ultimately this may lead to a better understanding of star formation in galaxies, and galaxy evolution in general. Aims. We aim to constrain the amount of star formation happening in long-lived clusters for four galaxies through the homogeneous, si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 63 publications
(90 reference statements)
9
109
0
1
Order By: Relevance
“…Right: Γ vs. star formation rate (SFR) surface density. Open blue diamonds correspond to the samples from Goddard et al (2010), green triangles to Adamo et al (2011), and red squares to Silva-Villa & Larsen (2011). The cyan crosses correspond to the sample of Cook et al (2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Right: Γ vs. star formation rate (SFR) surface density. Open blue diamonds correspond to the samples from Goddard et al (2010), green triangles to Adamo et al (2011), and red squares to Silva-Villa & Larsen (2011). The cyan crosses correspond to the sample of Cook et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…These measurements seem to show that the cluster formation efficiency (SCFE) increases with S SFR , although with considerable scatter (Cook et al 2012), and there have even been reports of no clear trend at all (Bastian 2008;Silva-Villa & Larsen 2011).…”
Section: Fraction Of Recent Star Formation Occurring In Clustersmentioning
confidence: 99%
“…Hence, two clusters with same physical parameters could host a different number of massive bright stars, resulting in very different integrated colors, especially in the A&A 581, A111 (2015) case of young and low-mass clusters that contain only a few massive bright stars. -SSP models are biased because they do not even match the average of integrated color distributions for star clusters with mass log 10 (M/M ) 4 (see, e.g., Fouesneau & Lançon 2010;Popescu & Hanson 2010;Silva-Villa & Larsen 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we use the Silva-Villa et al catalogue and select class 1 and 2 sources with ages 10 Myr and masses > 5000M⊙. The mass cut was applied in order to limit the effects of stochasticity of the stellar IMF in the broad band properties of the sources (e.g., Barbaro & Bertelli 1977;Fouesneau & Lançon 2010;Silva-Villa & Larsen 2011;de Meulenaer et al 2013). …”
Section: Cluster Cataloguementioning
confidence: 99%
“…The authors acknowledge that their apertures do not cover just individual clusters, but rather contain cluster complexes. In comparison, HST based optical studies typically have aperture sizes of 3-10 pc (e.g., Whitmore et al 2010;Silva-Villa & Larsen 2011). Randriamanakoto et al (2010 have tested the role of resolution in determining the luminosity function index of cluster/complexes, and found that decreasing the resolution led to mildly flatter luminosity functions (∼ 0.1 in the index), however the authors did not investigate how the lower resolution affected the derived cluster/complex properties.…”
Section: Introductionmentioning
confidence: 99%